Strategi Peningkatan Kualitas dan Stabilitas Guru Tidak Tetap dalam Konteks Pendidikan Tingkat Sekolah Dasar - Khoiruzzaim Kurniawan (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
This research aims to investigate and develop effective strategies to improve the quality and stability of non-permanent teachers in the context of primary school level education. Temporary teachers have a crucial role in creating a quality learning environment and making a significant contribution to student development. However, the challenges faced by non-permanent teachers, such as job insecurity and lack of access to regular training, can have a negative impact on the quality of their teaching and engagement in the educational process. This research methodology involves surveys, interviews, and documentation analysis to collect data from non-permanent teachers, school principals, and other stakeholders. The collected data will be analyzed qualitatively and quantitatively to identify the main challenges faced by non-permanent teachers and identify effective strategies to improve their quality and stability. It is hoped that the results of this research will provide in-depth insight into the factors that influence the quality and stability of non-permanent teachers in the context of primary school level education. In addition, this research will present strategic recommendations that can be implemented by schools, governments and educational organizations to improve working conditions and professional development of non-permanent teachers. Thus, it is hoped that this research can make a positive contribution to improving the quality of education at the primary level through improving working conditions and professional development of non-permanent teachers.